Мышление военное и гуманистичное в произведениях Млечны Шлях Кузьми Чорного, Pierwszy dzień wolności Леона Кручковского и Люди мы или нелюди Владимира Тендрякова - Oleander, Luiza (Acta Polono-Ruthenica, 2006)
In this article setting and literary decision of conflict, which appeared between war thinking and humanist thinking, are being traced through poetics, the character of development of literary- philosophic thought, which is directed to the defence of common to all mankind values, is determined.